Strengthening mechanisms in magnesium alloys containing ternary I, W and LPSO phases. Issue 7 (July 2018) - Tahreen, N.; Zhang, D.F.; Pan, F.S.; Jiang, X.Q.; Li, D.Y.; Chen, D.L.
Abstract: This study was aimed at identifying underlying strengthening mechanisms and predicting the yield strength of as-extruded Mg-Zn-Y alloys with varying amounts of yttrium (Y) element. The addition of Y resulted in the formation of ternary I (Mg3 YZn6 ), W (Mg3 Y2 Zn3 ) and LPSO (Mg12 YZn) phases which subsequently reinforced alloys ZM31 + 0.3Y, ZM31 + 3.2Y and ZM31 + 6Y, where the value denoted the amount of Y element (in wt%). Yield strength of the alloys was determined via uniaxial compression testing, and grain size and second-phase particles were characterized using OM and SEM. In-situ high-temperature XRD was performed to determine the coefficient of thermal expansion (CTE), which was derived to be 1.38 × 10 −5 K −1 and 2.35 × 10 −5 K −1 for W and LPSO phases, respectively. The individual strengthening effects in each material were quantified for the first time, including grain refinement, Orowan looping, thermal mismatch, dislocation density, load-bearing, and particle shearing contributions. Grain refinement was one of the major strengthening mechanisms and it was present in all the alloys studied, irrespective of the second-phase particles. Orowan looping and CTE mismatch were the predominant strengthening mechanisms in the ZM31 + 0.3Y and ZM31 + 3.2Y alloys containing I and W phases, respectively, while load-bearing and second-phase shearing were the salient mechanisms contributing largely to the superior yield strength of the LPSO-reinforced ZM31 + 6Y alloy.